Strategi Ekspansi Produksi Wuling Motors Tiongkok Di Indonesia pada Tahun 2020-2024 - Nabillah Irena Satedy; Resa Rasyidah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study analyzes the production base expansion strategy of Wuling Motors in Indonesia during the 2020–2024 period within the framework of Foreign Direct Investment (FDI) using the OLI paradigm (Ownership, Location, and Internalisation). This research employs a descriptive qualitative approach based on secondary data collected through a literature review. The findings indicate that Wuling Motors’ investment in Indonesia is driven by a market-seeking motive, supported by ownership advantages in capital and electric vehicle technology, location advantages including a large domestic market and pro-investment policies, and internalisation advantages through the establishment of an integrated manufacturing facility and internal supply chain control. The novelty of this study lies in applying the OLI paradigm to examine the expansion of a Chinese automotive manufacturer in Indonesia amid the electric vehicle industry transformation.